Grandmother role in Poland in a longitudinal perspective - Paula Pustulka (Studia z Teorii Wychowania)
Despite the fact that being a grandmother lasts longer and remains significant, relatively few empirical studies focus on the experience of being a grandmother in Poland today. Drawing on the findings of a qualitative longitudinal study, this article fills this knowledge gap and demonstrates a temporal evolution of the ‘grandmother’ social role. The results not only present the reflections connected to awaiting the first grandchild, but also describe the aspects of practical fulfillment of the grandmother role for the first time. The interviewed first-time grandmothers were navigating a repertoire of various social roles and, as grandmothers, they were mostly operating through company and engagement with their grandchildren.